Therapeutic efficacy and pharmacokinetics of liposomal-cannabidiol injection: a pilot clinical study in dogs with naturally-occurring osteoarthritis - Shilo-Benjamini, Yael; Lavy, Eran; Yair, Nadav; Milgram, Joshua; Zilbersheid, Daniel; Hod, Atara; Barasch, Dinorah; Abu Ahmad, Wiessam; Cern, Ahuva; Barenholz, Yechezkel (Frontiers in Veterinary Science, 2023)
Osteoarthritis is a common disease in dogs resulting in chronic pain and decreased wellbeing. Common analgesics such as non-steroidal anti-inflammatories may fail to control pain and can produce major adverse effects. Study objectives were to evaluate pharmacokinetics, therapeutic efficacy, and safety of subcutaneous liposomal-cannabidiol (CBD) as an additional analgesic therapy in dogs suffering from naturally-occurring osteoarthritis. Six such dogs were recruited following ethics approval and owner consent. Dogs were administered a single subcutaneous injection of 5 mg/kg liposomal-CBD. Plasma concentrations of CBD, blood work, activity monitoring collar data, wellbeing questionnaire (owners) and pain scoring (veterinarian) were performed at baseline and monitored up to six weeks following intervention. Data overtime were compared with baseline using linear-regression mixed-effects. P-value was set at 0.05. CBD plasma concentrations were observed for 6 weeks; median (range) peak plasma concentration (Cmax) was 45.2 (17.8-72.5) ng/mL, time to Cmax was 4 (2-14) days and half-life was 12.4 (7.7-42.6) days. Median (range) collar activity score was significantly increased on weeks 5-6; from 29 (17-34) to 34 (21-38). Scores of wellbeing and pain evaluations were significantly improved at 2-3 weeks; from 69 (52-78) to 53.5 (41-68), and from 7.5 (6-8) to 5.5 (5-7), respectively. The main adverse effect was minor local swelling for several days in 5/6 dogs. Liposomal-CBD administered subcutaneously produced detectable CBD plasma concentrations for 6 weeks with minimal side effects and demonstrated reduced pain and increase wellbeing as part of multimodal pain management in dogs suffering from osteoarthritis. Further placebo-controlled studies are of interest.